Determination of allelopathic noxious weed species as potential bioherbicide for weed control in Malaysia - Motmainna, Mst. (2021)
Continuous and indiscriminate use of synthetic herbicides has caused environmental pollution and the development of herbicide resistance weed. Allelopathic plants as natural herbicides could be a novel solution to reduce reliance on synthetic herbicides while also improving crop weed management. Noxious weeds have the potential to convey allelochemicals and influence the organisms around them. There is relatively little information available about the allelopathic activity of Malaysian noxious weed species. The discovery of unknown allelopathic noxious weeds in Malaysia could provide the way to develop new natural herbicides. In this regard, a variety of experiments were carried out in the lab and glasshouse to achieve the following goals; i) to assess the allelopathic activity of 30 noxious weed species in Malaysia ii) to determine the effects in laboratory and glasshouse; iii) to identify their allelopathic substance(s); iv) to determine the efficacy in comparison to the commercial herbicides, v) to evaluate the effect on physiological and biochemical changes of weeds. The experiment was conducted at the Seed Technology Laboratory, Crop Science, and Ladang 15, Universiti Putra Malaysia. A complete randomized design (CRD) with five replications and randomized complete block design (RCBD) with four replications were laid out for laboratory and glasshouse experiments. Experiment on the effects of methanolic extracts of 30-Malaysian noxious weed species (9 families) on the seeds survival rate and seedlings growth of Weedy rice (Oryza sativa f. spontanea Roshev) in the laboratory has been conducted. Five concentrations (6.25, 12.5, 25, 50 and 100 g L-1) of extracts were compared with control (distilled water). Parthenium hysterophorus L., Cleome rutidosperma DC. and Borreria alata (Aubl.) DC. proved strongly allelopathic compared to the other tested extracts. The phytotoxic effects of P. hysterophorus, C. rutidosperma and B. alata extract concentrations were further investigated and compared on survival rate and growth of crops (Zea mays L., Oryza sativa L., Abelmoschus esculentus L. Moench, Amaranthus gangeticus L.) and weeds (weedy rice, Echinochloa colona L. Link., Euphorbia hirta L. and Ageratum conyzoides L.) under laboratory and glasshouse conditions. Test plants were less sensitive to C. rutidosperma and B. alata than P. hysterophorus extract in both conditions (lab and glasshouse). Ageratum conyzoides, E. hirta, A. esculentus and A. gangeticus were mostly injured by P. hysterophorus extract at 100 g L-1 in the glasshouse. The LC-QTOF-MS/MS analysis has confirmed the presence of phenolic compounds (flavonoids, phenols, coumarins, carboxylic acids, benzoic acids), terpenoid, alkaloids, amino acids, fatty acids, piperazines, benzofuran, indole, amines, azoles, sulfonic acid and other unknown compounds in P. hysterophorus, C. rutidosperma and B. alata. The result indicated that methanol extract of C. rutidosperma and B. alata had fewer known phytotoxic substances than P. hysterophorus. A comparison study was conducted between P. hysterophorus extract (20, 40, and 80 g L-1), synthetic herbicide (glyphosate and glufosinate-ammonium at 2 L ha-1) as positive control and no treatment (negative control) on A. conyzoides, Weedy rice and Cyperus iria. No significant difference was obtained when P. hysterophorus extract (80 g L-1) and synthetic herbicides (glyphosate and glufosinate-ammonium) were applied on A. conyzoides. The response of physiological and biochemical properties of A. conyzoides, Weedy rice and C. iria was also investigated by the foliar application of P. hysterophorus at different concentrations (20, 40 and 60 g L-1). Physiological and biochemical properties of A. conyzoides were more sensitive to P. hysterophorus, especially at higher concentrations (60 g L-1). These results confirmed that P. hysterophorus have significant herbicidal effects for weed control. Hence it has the potential to be used as a bioherbicide to control weed in Malaysia.